2006
DOI: 10.3852/mycologia.98.4.541
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and ecology of dictyostelid cellular slime molds in Great Smoky Mountains National Park

Abstract: Great Smoky Mountains National Park encompasses an area of 2080 km2 in eastern Tennessee and western North Carolina between 35 degrees 28' and 35 degrees 47' N. Elevations are 270-2000 m above sea level, and the topography and vegetation are as diverse as any region of eastern North America. In 1998-2004 soil/litter samples for isolation of dictyostelid cellular slime molds were collected throughout the park. Collecting sites included examples of all major forest types along with the more common types of nonfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…5C ), three species were isolated from elevation 700–1,000 m, five species were isolated from elevation 1,000–1,300 m, six species were isolated from elevation 1,300–1,600 m, three species were isolated from elevation 1,600–1,900 m, and three species were isolated from elevation 1,900–2,200 m. We found that the number of species of dictyostelids increased at first and then decreased with increasing elevation. This is consistent with Landolt et al ( 55 ), who reported that elevation is negatively correlated with species abundance of dictyostelids. However, Paillet and Satre ( 51 ) found that the higher the elevation, the higher the dictyostelid species diversity.…”
Section: Discussionsupporting
confidence: 93%
“…5C ), three species were isolated from elevation 700–1,000 m, five species were isolated from elevation 1,000–1,300 m, six species were isolated from elevation 1,300–1,600 m, three species were isolated from elevation 1,600–1,900 m, and three species were isolated from elevation 1,900–2,200 m. We found that the number of species of dictyostelids increased at first and then decreased with increasing elevation. This is consistent with Landolt et al ( 55 ), who reported that elevation is negatively correlated with species abundance of dictyostelids. However, Paillet and Satre ( 51 ) found that the higher the elevation, the higher the dictyostelid species diversity.…”
Section: Discussionsupporting
confidence: 93%
“…This pattern fits the results reported by Landolt at al. ( 74 ), but not with what was reported by Paillet and Satre ( 75 ). Liu et al ( 25 ) investigated dictyostelid biodiversity in mountains at elevations >2,000 m and indicated that dictyostelids are probably common at higher elevations.…”
Section: Discussionmentioning
confidence: 56%
“…First, some studies of D. discoideum have concluded that population structure in D. discoideum is very low (Flowers et al, 2010), but these two populations are strongly genetically differentiated (Douglas et al, 2011). Second, the North Carolina site is in the southern Appalachians, a global hotspot for dictyostelids (Landolt et al, 2006), where there is high genetic diversity over small spatial scales (<1 cm) in the soil (Francis & Eisenberg, 1993;Fortunato et al, 2003b). By contrast, Texas forms the western edge of the D. discoideum species range, and near clonality has been observed at distances of 12 m in this region (Gilbert et al, 2009).…”
Section: Strainsmentioning
confidence: 99%